Deep Neck Infection: Atypical Presentation of Papillary Thyroid Cancer - Mahattanapreut, Apichana; Aroonroch, Rangsima; Chintrakarn, Chalermchai; Sriphrapradang, Chutintorn (Case Reports in Otolaryngology, 2021)
Deep neck infection is defined as an infectious process in the potential spaces and fascial plane of the neck which may result in a fatal complication. Prompt drainage and broad-spectrum antibiotics are the mainstays of treatment. Deep neck infection as the initial presentation of primary head and neck cancer is not common. Nevertheless, head and neck squamous cell carcinoma is the most common primary head and neck cancer, which could present with cervical metastasis and subsequently becomes infected. Papillary thyroid cancer has a naturally indolent course, and most patients present with a thyroid nodule. However, deep neck infection could be an uncommon presentation of papillary thyroid cancer which may obscure the diagnosis of underlying malignancy. This case report aims to present a rare presentation of papillary thyroid cancer which needs meticulous evaluation. Moreover, the pathological examination should be performed in all cases of deep neck infection for early detection and management of underlying papillary thyroid cancer.